CONTRIBUTION OF DUANO FISHERMAN WIFEIN INCREASING HOUSEHOLD INCOME IN TANJUNG PASIRVILLAGE TANAH MERAH SUB-DISTRICT INDRAGIRI HILIR REGENCY RIAU PROVINCE - Licia Dwi Oktari; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted in March 2019 in Tanjung Pasir Village, Tanah Merah sub-district, Indragiri Hilir Regency, Riau Province.The purpose of this study were to identify the types of activities, identify the factors of the wives of fishermen to work, and analyze the contributions of the fishermen's wives in increasing household economic income.The method used is the survey method whivh uses purposive sampling technique,with the total of respondents 18 people.The results showed that the activities of the wives of fishermen including Undomestik activities were 1 person daily kiosk (5.55%), 1 rice stall (5.55%), 1 people processed salted fish (5.55%), 1 shrimp paste processing people (5.55%), and Nipah broom makers as many as 2 people (11.11%) while the activities of fishermen's wives included in public activities are: Peeling ebi shrimp 1 person (5.55%), selling vegetables 1 person (5,55%), and Fishermen by 10people (55,55%).The contribution of Duano Tribe fishermen's wives in improving the household economy in Tanjung Pasir Village, Tanah Merah Subdistrict was in the Medium category of 36.83%. The factors that influence the Duano Fishermen's Wife in Tanjung Pasir Village to work are internal and external factors but in general are due to economic demands, especially after the husband's income decreases and expenditures are not in line with the husband's income, demanding the Duano Tribe Fisherman's wife to come to work.Keywords:Contributions, Domestic and Public Activities, Internal and external factors